Edge Computing Technology, Management and Integration - Goundar, Sam (IntechOpen, 2023)
Over the years, computing has moved from centralized location-based computing to distributed cloud computing. Because of cloud computing's security, regulatory, and latency issues, it was necessary to move all computation processes to the edge of the network (edge computing). However, at the edge, traditional computing devices no longer exist on their own. They have been joined by millions of mobile, Internet of Things (IoT), and smart devices, all needing computation. Therefore, edge computing infrastructure is necessary for multiple devices at the edge of the network. This book explores various technologies that make edge computing possible and how to manage computing at the edge and integrate it with existing networks and 5G networks of the future. It investigates the current state-of-the-art infrastructure and architecture and highlights advances and future trends. Security and privacy become a concern when you compute at the edge because the data needs to travel across various network nodes and user devices at the edge. As such, this book also discusses the management of security, privacy, and other network issues.